PEMBELAJARAN TAHFIDZUL QUR’AN BER-SANAD MELALUI METODE TALAQQI BERBASIS DIGITAL MOBILE LEARNING - Rohman, Dodik Fathur; Zulfitria, Zulfitria (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This study aims to examine the implementation of sanad-based Qur’anic memorization (tahfidzul Qur’an) learning through the talaqqi method integrated with digital mobile learning at Pondok Pesantren Tahfidzul Qur’an (PPTQ) Al-Kaukab. The background of this research lies in the urgency of preserving the sanad tradition in Qur’anic transmission while adapting to the advancement of digital technology, particularly in the context of remote learning. This study employs a qualitative descriptive method with a case study approach. The findings reveal that the use of mobile learning in the talaqqi method at PPTQ Al-Kaukab effectively bridges the authenticity of sanad-based teaching with the flexibility of modern education. Through digital applications, students (santri) can submit their memorization directly to certified teachers, maintaining accuracy in pronunciation and tajwid. Technical challenges such as internet stability and limited verbal interaction do arise but can be mitigated with improved system management and structured online schedules. This research recommends the further development of a more organized mobile-based learning system to support the sustainability of sanad-based tahfidz education in the digital era.